exMCAM-Fc, an S100A8/A9-mediated-metastasis blocker, efficiently reduced the number of circulating tumor cells that appeared in the blood flow - Tomonobu, Nahoko; Kinoshita, Rie; Sakaguchi, Masakiyo (Molecular biology reports, 2020)
Metastasis is the major cause of treatment failure in cancer patients and of cancer-associated death so that therapeutic regulation of metastasis is very important subject for the cancer treatment. We have been reported that S100A8/A9, a heterodimer complex of S100A8 and S100A9, and its receptors play a crucial role in the lung tropic cancer metastasis, i.e., S100A8/A9 is actively secreted from the lung when cancer mass exists even at remote area from the lung and then functions to attract the distant cancer cells to the lung since cancer cells own the S100A8/A9 receptor(s) on their cell surface. Interestingly, one of the newly developed decoys, exMCAM-Fc, a Fc fusion protein with the extracellular region of melanoma cell adhesion molecule (MCAM), one of the S100A8/A9 receptors, that could prevent the interaction of S100A8/A9 with MCAM, efficiently suppressed the lung tropic cancer metastasis through exerting the several inhibitory effects on the S100A8/A9-mediated cancer cell events including enhanced mobility, invasion and attachment to the endothelial cells. However, it still remains to clarify if the decoy will reduce the number of circulating tumor cells (CTCs) that are defined as substantial cells in the context of organ tropic cancer metastasis. Here, we first show that exMCAM-Fc effectively reduces the number of CTCs in the blood flow of the melanoma bearing mice. The novel finding reinforces the suppressive role of exMCAM-Fc on the cancer metastasis. We therefore expect that exMCAM-Fc may greatly contribute to reduce treatment failure by the efficient blocking of the life threatening cancer metastasis.